Sensitive Detection of Viral Antigens with a New Method, "Laser Magnet Immunoassay" - Mizutani, Hiroko; Suzuki, Miwako; Mizutani, Hiromichi; Fujiwara, Koichi; Shibata, Shuichi; Arishima, Koichi; Hoshino, Mitsutoshi; Ushijima, Hiroshi; Honma, Hitoshi; Kitamura, Takashi (MICROBIOLOGY and IMMUNOLOGY, 1991)
A new method, “laser magnet immunoassay”(LMIA), has been developed for sensitive detection of viral antigens. Target viruses captured on microbeads were made to react with antibodies labeled with magnetite particles. In a magnetic field, magnetically labeled antigens dispersed in water were attracted to and concentrated at one point on the surface, resulting in the lifting up of a small surface area. A laser beam which was incident on the point reflected, making an interference fringe. The intensity of the fringe indicates the amount of the magnetite conjugated with antigen. A very low concentration of antigens, such as 5 particles of influenza virus and 0.1pg/ml of human immunodeficiency virus (HIV) p24 antigen in human serum, could be detected by this method. Application of this method to diagnoses of viral diseases in early stages is discussed.